Utilization of Learning Technology as Part of Infrastructure Standards in Quality Assurance and Control of Community Education at PKBM Ar Royyan Pekanbaru - Amanda A; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article aims to analyze the use of learning technology as part of the standard facilities and infrastructure to support the assurance and quality controlof community education at the Ar Royyan Community Learning Center (PKBM) in Pekanbaru. This study uses a qualitative approach with primary data collection through interviews with the Head of the Ar Royyan Community Learning Center (PKBM). The results show that the use of learning technology at the Ar Royyan Community Learning Center (PKBM) in Pekanbaru, such as computers, digital learning media, internet access, and learning applications, can improve the effectiveness and quality of the learning process in the community education program. Learning technology also helps tutors deliver material more interactively, expands access to learning resources, and supports more systematic learning evaluations. Furthermore, the use of learning technology also plays a role in supporting the implementation of the community education quality assurance and control system.